Effectiveness of Legal Protection for Workers in the Work From Home or Remote Work System - Wilson Wibowo; Gunardi Lie (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Technological advancements have fundamentally reconfigured traditional labor patterns into remote working systems, creating a new set of legal implications for employee protection. This inquiry focuses on assessing the legal effectiveness of protections afforded to remote workers within the Indonesian jurisdiction. Utilizing normative legal research with a library-based approach, the study examines the relevant statutory and conceptual foundations. The analysis reveals a significant legal vacuum, as WFH protocols remain largely unaddressed in Law No. 13 of 2003 and its subsequent amendment via Law No. 11 of 2020. This lack of specific regulation compromises the fulfillment of labor rights, including work-life boundaries, fair compensation for overtime, and personal privacy. Moreover, the study identifies lax enforcement and asymmetrical bargaining power as critical barriers to legal efficacy. Ultimately, the research suggests that current protections are inadequate and calls for a more responsive legislative framework to accommodate the complexities of the modern digital workforce.